Eimeria species in cattle with diarrhoea in the Republic of Korea regarding age, season and nature of diarrhoea. (27th October 2018) - Lee, Seung‐Hun; Kim, Ha‐Young; Lee, Haeseung; Kim, Jong Wan; Lee, Yu‐Ran; Chae, Myeong Ju; Oh, Sang‐Ik; Kim, Jong Ho; Rhee, Man Hee; Kwon, Oh‐Deog; Goo, Youn‐Kyoung; Kim, Tae‐Hwan; et al.
Abstract : This study evaluated the prevalence of Eimeria species, particularly E bovis, E zuernii and E auburnensis that are pathogenic to cattle, in faecal samples collected from cattle with diarrhoea reared in the Republic of Korea by using microscopy and PCR. In addition, the prevalence of Eimeria species was analysed according to age, type of cattle, region, season and nature of diarrhoea. Overall, Eimeria species were identified in 279 of the 1261 (22.1 per cent) faecal samples through microscopy, and statistical analysis revealed a lower prevalence in calves aged than three weeks or less and higher prevalence in cattle with haemorrhagic diarrhoea. Of the 279 microscopy‐positive samples, E bovis, E zuernii and E auburnensis were identified in 100 (7.9 per cent), 83 (6.6 per cent) and 27 (2.1 per cent) faecal samples, respectively, by using PCR. To the authors' knowledge, this study is the first to apply PCR for epizootiology of bovine coccidiosis.